2009
DOI: 10.1038/leu.2009.206
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dynamics of human cord blood-derived CD34− SCID-repopulating cells using intra-bone marrow injection

Abstract: The identification of human CD34-negative (CD34 À ) hematopoietic stem cells (HSCs) provides a new concept for the hierarchy in the human HSC compartment. This study investigated the long-term repopulating capacity and redistribution kinetics of human cord blood-derived CD34 À severe combined immunodeficiency (SCID)-repopulating cells (SRCs) and compared them with those of CD34 þ CD38 þ and CD34 þ CD38 À SRCs using the intra-bone marrow injection (IBMI) to clarify the characteristics of CD34 À SRCs. On the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…Xenotransplantation of human UCB HPCs into mice utilizing direct IB-injection achieves superior long-term engraftment and the ability for secondary SCID mouse repopulation (22)(23)(24). These preclinical small-animal models cannot predict engraftment kinetics in humans undergoing IB-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…Xenotransplantation of human UCB HPCs into mice utilizing direct IB-injection achieves superior long-term engraftment and the ability for secondary SCID mouse repopulation (22)(23)(24). These preclinical small-animal models cannot predict engraftment kinetics in humans undergoing IB-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…21, 22, 23 Moreover, our in vivo kinetic analysis clearly demonstrated that only one or two CD34 − SRCs had potent human hematopoietic cell reconstitution potentials, which was almost equivalent to that of 5–10 CD34 + CD38 − SRCs. 24, 25 Using this highly efficient SRC assay, we demonstrated that the surface immunophenotype of CD34 − SRCs is Lin − CD34 − c-kit − flt3 − . 23, 26 However, the frequency of CD34 − SRCs in these 13Lin − CD34 − cells is approximately 1/25 000, which is still very low in comparison to the frequency (1/40) of CD34 + CD38 − SRCs in 13Lin − CD34 − cells.…”
Section: Introductionmentioning
confidence: 95%
“…As reported previously, CB-derived CD34 − SRCs could produce CD34 + SRCs in vitro (7,(11)(12)(13)41). In order to investigate whether DPSCs and BM-MSCs have the potential to support human hematopoietic stem/progenitor cells (HSPCs) in vitro, 2,000 human CB-derived 18Lin − CD34 + or 18Lin − CD34 − cells (shown in factor (G-CSF)] for 1 week.…”
Section: Hspc-supporting Potential Of Dpscs and Bm-mscsmentioning
confidence: 99%
“…Then, the SRC activities of human CB-derived 18Lin − CD34 + and 18Lin − CD34 − cells cocultured with mouse BM-MSCs or DPSCs were evaluated using NOG mice as reported previously (7,(11)(12)(13)41). Human CBderived 18Lin − CD34 + or 18Lin − CD34 − cells cocultured with mouse BM-MSCs, DPSCs, or without feeder cells were transplanted into NOG mice by the IBMI method.…”
Section: Src Activities Of 18lin − Cd34 + and 18lin − Cd34 − Cells Comentioning
confidence: 99%